Genealogi Moderasi Beragama Pada Masyarakat Transmigran Jawa Dan Bali Dengan Penduduk Asli Di Lampung Tengah Tahun 1950-1998 - Budianto, Aan (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
The Terbanggi Besar area in Central Lampung has developed despite having three different community groups. These three communities are the indigenous Lampung people, migrants from Java Island, and migrants from Bali Island. Bandar Jaya Market has become the main meeting point for harmonious interaction among these three communities as a manifestation of religious moderation. This study will explore the genealogy of the practice of religious moderation among these communities using historical research methods. The findings of this study indicate that the life philosophy of these three communities is the root of religious moderation practices. The harmonious social relationships between the indigenous Lampung people, Javanese, and Balinese migrants have contributed to a more advanced economy in Terbanggi Besar compared to other areas in Central Lampung. Cultural acculturation also occurs due to the openness factor rooted in the life philosophy of each community—Lampung, Javanese, and Balinese.